Pembinaan Akhlaq Mulia Melalui Baca Tulis Al-Qur'an Untuk Mewujudkan Siswa yang Berkarakter di SMP Islam Terpadu Al-Madinah Tahun Pelajaran 2020-2021 - Rohmah, Neng; Sauri, Sofyan; Sukandar, Ahmad (Magister Pendidikan Agama Islam Universitas Islam Nusantara, 2022)
Education and moral development for students is very important so that they have noble character and are trained to like goodness so that good deeds will easily be born from it. In the letter Q.S. al-Hasyr/59 Allah SWT ordered to always follow in the footsteps of the Prophet Muhammad. Philosophically, this research is based on the theory developed by Skinner, especially related to behavior (behavior) which is considered relatively applicable in the formation of behavior. Moral development is the first focus of attention in Islam. This is in accordance with the morality of the Prophet Muhammad SAW to perfect noble character. This study aims to 1) want to know the implementation of noble character development through reading and writing the Qur'an to create students with character. 2) want to know the evaluation of noble character development through reading and writing the Qur'an to create students with character. 3) want to know the factors supporting and inhibiting the development of noble character through reading and writing the Qur'an to create students with character. The method of this research approach is descriptive qualitative research. Data collection techniques are by using the method of observation, interviews and documentation. Data analysis uses the collection of: 1) data (Data Collection), 2) data reduction (Data Reduction), 3) data display, verification and Confirmation of Conclusions (Conclusion Drawing and Verification). The results showed that: 1). a) The results showed that the learning planning carried out by the PAI teachers which consisted of the application of schedules, methods, mastery of materials and preparation of learning equipment in class VIII of SMP Islam Terpadu Al-Madinah had been carried out smoothly. 2) the implementation of noble character development in class VIII of the Integrated Islamic Junior High School Al-Madinah for the 2020-2021 academic year has been carried out well. The teacher has accustomed students to carry out reading and writing activities of the Koran well, 3). The evaluation used by PAI teachers, namely the evaluation of the CIPP (Context, Input, Process, and Product) model is one of several existing evaluation models such as the formative-summative model evaluation, 4). The constraint factor is from parents who do not pay attention to students when students are at home, and the lack of facilities in the form of a mosque that is not wide enough so that it is crammed into the mosque and students do not focus on learning to read and write the Koran. the solution is that teachers and parents work together in educating students, and schools provide a comfortable place in learning to read and write the Qur'an by expanding the mosque.